Boolean semiring key-exchange with BLAKE3 security (BKEX-B3) - Alvary Kefas Kwala; Alpna Mishra; Shri Kant (Discover Computing, 2025)
Abstract Quantum computing has become a major threat to most classical cryptosystems, especially RSA and ECC cryptosystems. Thus, a new field, Post-Quantum Cryptography (PQC), has come to light, aiming to create protocols that cannot be susceptible to quantum attacks. This work presents a new Boolean Semiring Key Exchange Protocol combined with BLAKE3 cryptographic hash function (BKEX-B3). The protocol leverages the flexibility of BLAKE3’s eXtendable Output Function (XOF) and the nonlinearity of Boolean algebra to produce a flexible, quantum-resistant solution capable of dynamically adapting security levels to advancement in quantum algorithms. An examination of the protocol’s performance reveals that it outperforms modern algorithms, especially in terms of memory efficiency and runtime, such as Kyber512, HQC-128, BIKE-L1, sntrup761, FrodoKEM-640-SHAKE, and NewHope. Its scalability and efficient resource management make it a highly appropriate solution that is adaptable and secure for the post-quantum era in environments with limited resources, such as the Internet of Things.